Pelatihan Pembuatan Hand Sanitizer Untuk Guru SMPN 1 Banyuresmi Garut Pada Masa Adaptasi Kebiasaan Baru (AKB) - Indra Dodo Saputra; Leni Sri Mulyani; Chevi Ardiana; Tati Kristianti (Jurnal Pekemas, 2020)
Health is a very important aspect of life. One of ways to maintain it by taking care of your hands. A Hand sanitizer (antiseptic tangan) is a health’s product that can instantly kill microorganisms without using water and it can be used anytime and anywhere. The purpose of these dedications realizes one of the Tri Dharma colleges, socializes Clean and Healthy Living habits (PHBS) and it can produce a hand sanitizer that can be used properly for oneself, families, educational institutions and the surrounding societies. The method uses explanatory material and the practice of making hand sanitizers. The data analysis technique uses descriptive. The result of this dedications are the participants' understanding of the manufacture of hand sanitizer, the functions of hand sanitizer and the application of clean and healthy living habits